The potential role of gut microbiota outer membrane vesicles in colorectal cancer - Meng, Ran; Zeng, Minmin; Ji, Ying; Huang, Xinxiang; Xu, Min (Frontiers in Microbiology, 2023)
Colorectal cancer (CRC) is a common malignant digestive tract tumor in colorectal regions.Considerable evidence now shows that the gut microbiota have essential roles in CRC occurrence and development. Most Gram-negative bacteria release outer membrane vesicles (OMVs) via outer membrane blistering, which contain specific cargoes which interact with host cells via intercellular communications, host immune regulation, and gut microbiota homeostasis. Studies have also shown that OMVs selectively cluster near tumor cells, thus cancer treatment strategies based on OMVs have attracted considerable research attention. However, little is known about the possible impact of gut microbiota OMVs in CRC pathophysiology. Therefore, in this review, we summarize the research progress on molecular composition and function of OMV, and review the microbial dysbiosis in CRC. We then focus on the potential role of gut microbiota OMVs in CRC. Finally, we examine the clinical potential of OMVs in CRC treatment, and their main advantages and challenges in tumor therapy.